(untitled) (Research, Society and Development, 2020)
Objective: to identify the demand for care in the emergency care service (PA). Methodology: cross-sectional, retrospective and quantitative research, carried out based on the CID (International Statistical Classification of Diseases) registry registered in the G-HOSP system of patients seen at the PA of a Pediatric Hospital in 2018. Monthly data, gender, age (including patients from 0 to 15 years, 11 months and 29 days), place of residence and the top 5 CID were selected. Results: the highest number of visits per day occurred in April and the lowest in January; 50.42% of the patients were male; greater number of visits was to lactating patients; most of the visits are not declared, among those declared, most of the visits are described as general medical examination, acute nasopharyngitis, routine examination of the child, unspecified upper airway infection and unspecified acute tonsillitis. Final considerations: the main reason for medical care was the general medical examination for the most of the year. It was observed that the younger the child, the greater the need for care. It is necessary to assess the risk stratification of patients before medical care.